2019
DOI: 10.2147/cmar.s224711
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel Scoring System for Patients with Recurrence of Hepatocellular Carcinoma After Undergoing Minimal Invasive Therapies</p>

Abstract: Background: The higher recurrence rate of hepatocellular carcinoma (HCC) needs to be urgently controlled. However, definitive markers are lacking for patients with recurrence of HCC after undergoing minimal invasive therapies-local ablation combined with transcatheter arterial chemoembolization (TACE). Materials and methods: Demographic and clinicopathological data of 234 subjects receiving combined therapies as the initial treatment were retrospectively analyzed. Univariate and multivariate Cox regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Another limitation of this study was that the total number of patients analyzed was relatively small, with a comparatively short follow-up period. Our previous studies showed that early recurrence often occurs in the first 2-3 years after ablation, making up about 70% of recurrence events ( 19 ). Moreover, as an interim analysis, our study is not concluded here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another limitation of this study was that the total number of patients analyzed was relatively small, with a comparatively short follow-up period. Our previous studies showed that early recurrence often occurs in the first 2-3 years after ablation, making up about 70% of recurrence events ( 19 ). Moreover, as an interim analysis, our study is not concluded here.…”
Section: Discussionmentioning
confidence: 99%
“…All patients classified as China liver cancer staging (CNLC) I a, I b, II a, or II b satisfied the criteria of Class A or B of the Child-Pugh classification and had an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1. Only high relapse-risk patients were included, which was evaluated by a scoring system ( 19 )established in our previous research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients enrolled received TACE combined with locoregional ablation, and the latter was conducted under computed tomography (CT) or magnetic resonance imaging (MRI) guidance within 2 weeks after TACE. The operational steps of the two interventions have been described in detail in the previous articles of our team, so we won’t go into them here ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above background, our team developed a novel scoring system built on account of HCC patients diagnosed between 2015 and 2016 to predict the risk of recurrence after local treatment, and it has achieved a good response in clinical use (13). The patients were stratified into low, intermediate, and high-risk groups of recurrence according to predicted probability, with significant statistical differences in RFS among different subgroups.…”
Section: Introductionmentioning
confidence: 99%